Influence of Vegetation Change on Watershed Hydrology: Implications for Paleoclimatic Interpretation of Lacustrine d180 Records - Rosenmeier, M. F.; Hodell, D. A.; Brenner, M.; Curtis, J. H.; Martin, J. B.; Anselmetti, F. S.; Ariztegui, D.; Guilderson, T. P. (Journal of Paleolimnology, 2002)
id: 1386

Abrupt climate change and pre-Columbian cultural collapse - Brenner, M.; Hodell, D. A.; Curtis, J. H.; Rosenmeier, M.; Binford, M. W.; Abbott, M. B. (Interhemispheric Climate Linkages, 2001)
id: 1408

Climate change in the circum-Caribbean (late Pleistocene-to-Present) and implications for regional biogeography - Curtis, J. H.; Brenner, M.; Hodell, D. A. (Biogeography of the West Indies: Patterns and Perspectives, 2nd Edition, 2001)
id: 265

Climate change in the northern American tropics since the last ice age: implications for environment and culture (Book Section) - Hodell, D. A.; Brenner, M.; Curtis, J. H. (Imperfect Balance: Landscape transformations in the Precolumbian Americas, 2000)
id: 198

Climate change in the Lake Valencia Basin, Venezuela, approximately 12,600 yr BP to present - Curtis, J. H.; Brenner, M.; Hodell, D. A. (The Holocene, 1999)
id: 197

Paleoclimate of Southwestern China for the past 50,000 yr inferred from lake sediment records - Hodell, D. A.; Brenner, M.; Kanfoush, S. L.; Curtis, J. H.; Stoner, J. S.; Song, X. L.; Yuan, W.; Whitmore, T. J. (Quaternary Research, 1999)
Long sediment cores (12.5 and 13.5 m) from two lakes in Yunnan Province were used to infer the paleoclimate of southwest China over the past 50,000 yr, During the Holocene and marine isotope stage (MIS 3), bio-induced carbonate precipitation and organic matter (OM) production was high, suggesting warm temperatures and high primary productivity. In contrast, sediment inorganic carbon (IC) and organic carbon (OC) concentrations were low in last glacial deposits from 38,000 to 12,000 cal yr B.P., indicating cool temperatures and low productivity. The 50,000-yr record has alternating peaks of carbonate and coarse-grain (>38 mu m) quartz that reflect warm, moist interglacial or interstadial conditions alternating with cold, dry glacial or stadial conditions, respectively. Spectral analysis of the carbonate and quartz signals reveals power concentrated at periods of 7200 and 8900 cal yr, respectively, that may reflect a nonlinear climate response to precessional forcing at a time of reduced eccentricity modulation (McIntyre and Molfino, 1996). Oxygen isotope values of calcite from Yunnan lake cores indicate the summer monsoon was weak during the last glaciation from 50,000 to 12,000 cal yr B.P. The summer monsoon intensified between 12,000 and 8000 cal yr B.P., but weakened gradually in response to insolation forcing during the mid-to-late Holocene. Our results support the Overpeck ef al. (1996) model that posits a weak summer monsoon during the last glaciation that responded nonlinearly to insolation forcing when its intensity was affected by Eurasian snow cover and ice-sheet extent. The summer monsoon intensified and responded linearly to seasonal insolation forcing in the Holocene when ice volume diminished. (C) 1999 University of Washington.
255ltTimes Cited:85Cited References Count:58

Controls of chemical and isotopic composition of Lake water, Peten, Guatemala and implications for Holocene climatic variability in Central America. Abstracts with Programs - Martin, J. B.; Rosenmeier, M. F.; Hodell, D. A.; Brenner, M.; Curtis, J. H. (Geological Society of America Annual Meeting, 1998)
id: 140

Late Holocene climatic variability in Central America: evidence from lacustrine sediments in the Peten, Guatemala and implications for Maya cultural evolution; Procedings of the PEP 1 - Rosenmeier, M. F.; Hodell, D. A.; Martin, J. B.; Brenner, M.; Curtis, J. H. (PEP 1 (Pole-Equator-Pole, Paleoclimate of the Americas), 1998)
id: 141

A multi-proxy study of Holocene environmental change in the Maya lowlands of Peten, Guatemala - Curtis, J. H.; Brenner, M.; Hodell, D. A.; Balser, R. A.; Islebe, G. A.; Hooghiemstra, H. (Journal of Paleolimnology, 1998)
We used multiple variables in a sediment core from Lake Peten-Itza, Peten, Guatemala, to infer Holocene climate change and human influence on the regional environment. Multiple proxies including pollen, stable isotope geochemistry, elemental composition, and magnetic susceptibility in samples from the same core allow differentiation of natural versus anthropogenic environmental changes. Core chronology is based on AMS (14)C measurement of terrestrial wood and charcoal and thus avoids the vagaries of hard-water-lake error. During the earliest Holocene, prior to similar to 9000 (14)C yr BP, the coring site was not covered by water and all proxies suggest that climatic conditions were relatively dry. Water covered the coring site by similar to 9000 (14)C yr BP, coinciding with filling of other lakes in Peten and farther north on the Yucatan Peninsula. During the early Holocene (similar to 9000 to similar to 6800 (14)C yr BP), pollen data suggest moist conditions, but high delta(18)O values are indicative of relatively high E/P. This apparent discrepancy may be due to a greater fractional loss of the lake's water budget to evaporation during the early stages of lake filling. Nonetheless, conditions were moist enough to support semi-deciduous lowland forest. Decrease in delta(18)O values and associated change in ostracod species at similar to 6800 (14)C yr BP suggest a transition to even moister conditions. Decline in lowland forest taxa beginning similar to 5780 (14)C yr BP may indicate early human disturbance. By similar to 2800 (14)C yr BP, Maya impact on the environment is documented by accelerated forest clearance and associated soil erosion. Multiple proxies indicate forest recovery and soil stabilization beginning similar to 1100 to 1000 (14)C yr BP, following the collapse of Classic Maya civilization.
Zj856Times Cited:92Cited References Count:96

A Holocene vegetation history from lowland Guatemala - Islebe, G. A.; Hooghiemstra, H.; Brenner, M.; Curtis, J. H.; Hodell, D. A. (Holocene, 1996)
A 5.45-m core from Lake Peten-Irza, lowland Guatemala, contains a near-complete record of Holocene sedimentation. The age-depth relationship for the core is based on AMS C-14 dating of terrestrial wood fragments and provides a reliable chronology in this karst region where hard-water lake error has typically confounded sediment geochronology. In the basal part of the sequence, pollen of the Moraceae-Urticaceae group dominate, indicating the presence of widespread tropical forest during the early Holocene (c. 8600-5600 yr BP). Relative abundance of pollen of high forest taxa declined beginning as early as 5600 yr BP, indicating climatic drying or perhaps initial land clearance. Deforestation by prehistoric Mayan inhabitants is documented clearly in the pollen record beginning about 2000 pr BP (106 cal BC-122 cal Ao, 95.4%, 2 sigmas) by the appearance of disturbance taxa (e.g. Ambrosia and Poaceae) and presence of Zea. Forest regrowth occurred following the Classic Maya collapse, c. AD 900, as reflected by a relative increase in Moraceae-Urticaceae pollen.
Vh189Times Cited:103Cited References Count:44

Possible Role of Climate in the Collapse of Classic Maya Civilization - Hodell, D. A.; Curtis, J. H.; Brenner, M. (Nature, 1995)
THE Maya civilization developed around 3,000 years ago in Mesoamerica, and after flourishing during the so-called Classic period, it collapsed around 750-900 AD(1). It has been speculated(2-6) that climate change may have played a part in this collapse. But efforts to reconstruct the last three millennia of Mesoamerican climate using palynological methods have met with equivocal success, because human-mediated deforestation has altered regional vegetation in ways that mimic climate shifts, making it difficult to discriminate between natural and anthropogenic changes(7-15). Here we use temporal variations in oxygen isotope and sediment composition in a 4.9-m sediment core from Lake Chichancanab, Mexico, to reconstruct a continuous record of Holocene climate change for the central Yucatan peninsula. The interval between 1,300 and 1,100 yr up (AD 800-1,000) was the driest of the middle to late Holocene epoch, and coincided with the collapse of Classic Maya civilization, This continuous climate proxy record thus provides evidence of climate deterioration in the Maya region during the terminal Classic period.
Rb101Times Cited:439Cited References Count:41